2001
DOI: 10.1074/jbc.m010991200
|View full text |Cite
|
Sign up to set email alerts
|

Residues within the N-terminal Domain of Human Topoisomerase I Play a Direct Role in Relaxation*

Abstract: All eukaryotic forms of DNA topoisomerase I contain an extensive and highly charged N-terminal domain. This domain contains several nuclear localization sequences and is essential for in vivo function of the enzyme. However, so far no direct function of the N-terminal domain in the in vitro topoisomerase I reaction has been reported. In this study we have compared the in vitro activities of a truncated form of human topoisomerase I lacking amino acids 1-206 (p67) with the full-length enzyme (p91). Using these … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
68
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(72 citation statements)
references
References 43 publications
(49 reference statements)
4
68
0
Order By: Relevance
“…This region is included in the N-terminal domain of the enzyme that in general is dispensable for both relaxation and binding of camptothecin [14,15]. However, detailed studies have recently revealed that the N-terminal domain influences the rate of relaxation and sensitivity of the enzyme to camptothecin [16].In the present work we report that the natural substrate for the kinase activity of htopo I, SF2/ASF protein, inhibits camptothecin-induced DNA cleavage by the enzyme. This effect results from reduced amount of the cleavable complex formed by htopo I in the presence of SF2/ASF.…”
mentioning
confidence: 57%
See 3 more Smart Citations
“…This region is included in the N-terminal domain of the enzyme that in general is dispensable for both relaxation and binding of camptothecin [14,15]. However, detailed studies have recently revealed that the N-terminal domain influences the rate of relaxation and sensitivity of the enzyme to camptothecin [16].In the present work we report that the natural substrate for the kinase activity of htopo I, SF2/ASF protein, inhibits camptothecin-induced DNA cleavage by the enzyme. This effect results from reduced amount of the cleavable complex formed by htopo I in the presence of SF2/ASF.…”
mentioning
confidence: 57%
“…Elimination of a dissociation of htopo I as a rate-limiting step for relaxation can be achieved by decreasing the DNA/htopo I ratio during the relaxation to 1 : 1 or less [16]. However, in this case the reaction rate should be slowed because of an elevated amount of the enzyme [16]. We achieved this by reducing the reaction temperature to 0°C.…”
Section: Effect Of Sf2/asf On Dna Relaxationmentioning
confidence: 99%
See 2 more Smart Citations
“…This domain distinguishes eukaryotic topoisomerase I from a minimal variant encoded by vaccinia virus (24) and from other microbial recombinases more distantly related (25). It contributes scarcely to the activity of the enzyme in vitro (26), but it is believed to determine the biological properties of topoisomerase I. Most notably, it seems to be a docking place for interacting proteins, such as nucleolin (27).…”
Section: Discussionmentioning
confidence: 99%